Manoj Mitra'er Natoke Prantoborger Swar O Droher Swaroop: 'Chak Bhanga Madhu' (Jagannath University Journal of Arts, 2026)
The role and contribution of Manoj Mitra (1938–2024) in Bengali drama remain unparalleled. His plays do not merely depict stories; rather, they serve as socio-political commentaries, highlighting the struggles of marginalized communities and exposing the inherent class conflict, exploitation, and systemic oppression present in society. His deep engagement with the theatre and his experience as an actor infused his works with realism and theatrical dynamism. His dramas resonate with political awareness and social consciousness. His theatrical framework stands apart for its deep-rooted engagement with the human condition, offering profound insights into power structures, survival, and rebellion.Among his most significant works, Chak Bhanga Madhu stands out as a masterpiece of social realism and class struggle. Written in 1969 and staged in 1972, this play critically examines the exploitation of the working class, highlighting their resilience and spirit of defiance. Through its characters and narrative, Mitra crafts a powerful critique of the capitalist system while simultaneously exploring the psychology of rebellion and resistance.This article attempts to analyze Chak Bhanga Madhu in the broader context of socio-economic situation of our society. It delves into how Manoj Mitra conceptualized the struggle of the oppressed, how he infused his drama with artistic depth, and how his unique storytelling technique brought forth the realities of social conflict and resistance. Keeping the concept of class struggle at the forefront, this study explores how the emergence of rebellion among the exploited is dramatized in Mitra’s work. By analyzing the artistic and theatrical dimensions of Chak Bhanga Madhu, this article aims to highlight Mitra’s legacy as a playwright who used theatre as a means of social critique and cultural transformation.Jagannth University Journal of Arts, v-15, i-01, 2025: p01-12